Ice Forces on Vertical Piles - Nevel, D E; Perham, R E; Hogue, G B (1977)
The amount of force that an ice sheet can apply to a vertical pile was tested by lowering a hydraulic ram device into a hole cut in an existing sheet. The device had a large base and shoved a relatively narrow vertical pile in a horizontal direction. Test variables were: pile widths - 1.5 in. to 36.7 in.; pile shapes-flat, round, 45 and 90 wedges; ice thickness - 2.6 in. to 8.8 in.; and ram speed - 0.07 in./sec to 18.75 in./sec; but not all shapes and sizes were tested at all speeds. Air temperature was 20 F(-6.7 C). Forces and displacements were measured electronically. The findings are presented as a table of test results and as bar graphs of the resultant ice pressures versus the pile width-to-ice-thickness ratio, pile width and shape combination and pile velocity. The types of failures in the ice sheet were classified as crushing, splitting, buckling, bending, and creeping. The ice sheet generally withstood a high initial load followed by several lower peak load levels. The maximum ice pressure measured was 610 psi for a 12.6-in.-diam round pile in 8.4-in.-thick ice.